X-ray magnetic circular dichroism and hard X-ray photoelectron spectroscopy of tetragonal Mn72Ge28 epitaxial thin film. (23rd March 2018) - Kim, Jinhyeok; Mizuguchi, Masaki; Inami, Nobuhito; Ueno, Tetsuro; Ueda, Shigenori; Takanashi, Koki
Abstract: An epitaxially grown Mn72 Ge28 film with a tetragonal crystal structure was fabricated. It was clarified that the film had a perpendicular magnetization and a high perpendicular magnetic anisotropy energy of 14.3 Merg/cm 3 . The electronic structure was investigated by X-ray magnetic circular dichroism and hard X-ray photoelectron spectroscopy. The obtained X-ray magnetic circular dichroism spectrum revealed that the Mn orbital magnetic moment governed the magnetocrystalline anisotropy of the Mn72 Ge28 film. A doublet structure was observed for the Mn 2p3/2 peak of hard X-ray photoelectron spectrum, indicating the spin exchange interaction between the 2p core-hole and 3d valence electrons.